Psychological Narrative and Archetypal Resonance: A Study on the Guiding Framework for Script Creation of 3D Animation Based on Chinese Folk Hero Mythology - Tong Zhang; Harryizman Harun; Norhana Yusof (Environment and Social Psychology, 2025)
The paper explains how consumer psychology, archetypal narrative structures and the Chinese folk hero mythology converged to create a script development framework to serve script production within the 3D animation. The paper analyzes how the mythological figures (e.g., Nezha, Sun Wukong, and Mulan) apply the psychological processes that activate the emotional involvement and consumer behavior. Based on the Narrative Transportation Theory, the study will show that highly immersive stories, built around universal archetypes, help to identify the audience, memorize, and be attached to the brand. The analysis incorporating the perspectives of narrative psychology, emotional branding, and symbolic consumption, the paper creates a five-stage scriptwriting system that correlates plot development and character progression with consumer affective stimuli. The case studies of the Chinese folk heroes show that their mythic roles can be well related with the contemporary spectators especially with the elements of defiance, change, and dignity. These archetypes do not just offer a symbolic meaning, but also affect actual consumer behavior including rewatching, sharing of content and buying merchandise. The paper takes a final suggestion of developing a modular system of developing 3D animation scripts that are culturally specific but psychologically universal, providing the theoretical and applied basis. The work is a part of the developing sphere of media psychology and animation research, where the ancient mythology can be applied to the emotionally intelligent narration in modern digital space.